Promoting "Difabel", Promoting Social Model of Disability in Indonesia, Study of Disability Movement in Yogyakarta - Slamet Thohari (Brawijaya Journal of Social Science, 2019)
For many decades, disability in Indonesia has been seen in medical perspective, segregated into special schools and their presences regarded as a social pathology. However, social model concept of disability defining disability as a product of social oppression, gave tremendous effect to deconstruct the term for â€œdisabled personsâ€ which is in Indonesian means â€œpenyandang cacatâ€. Inspired by social model, the Indonesian disability movement tried to change it into DIFABEL which means â€œdifferently-abled-people.Â  The research was done in Yogyakarta before Indonesia ratifying the Convention on The Rights of Person with Disabilities, 2011. The findings are the disability movement got their momentous moment in changing the new paradigm in Indonesian presidential election, 2004. DPOs which have been engaged to this issue underwent fragmentation into many aspects, they also bequeathed into next generation concerning disability issues.